Science and Processing of Cast Iron XI - Attila Diószegi; Vasile Lucian Diaconu; Anders E.W. Jarfors (Trans Tech Publications Ltd, 2018)
11th International Symposium on the Science and Processing of Cast IronSelected, peer reviewed papers from the 11th International Symposium on the Science and Processing of Cast Iron (SPCI-XI), September 4-7, 2017, Jönköping, Sweden